Studies on Eyelid Reconstruction - Mago, Vishal (New Frontiers in Medicine and Medical Research Vol. 9, 2021)
Eyelid reconstruction is a challenging procedure demanding technical skill and expertise. 15 eyelid defects were reconstructed in Plastic Surgery Department, bps govt Medical College for women, Sonepat with satisfactory results using various techniques according to the defect and following the basic principles outlined by Mustarde.